Histopathological study of diclofenac induced acute renal failure under lipoic acid and bosentan therapy in male albino rats - Lina Bahjat Qasim; Ghaith A. Jasim; Ihsan S. Rabeea (College of Pharmacy / Mustansiriyah University, 2022)
Acute kidney injury (AKI), formly known as acute renal failure (ARF), is an abrupt and reversible decrease in kidney function as indicated by the glomerular filtration rate (GFR). Diclofenac-induced AKI is due to toxic effect of it on renal glomeruli, resulting in glomerular lesions. Furthermore, diclofenac causes autolysis, which increase renal intracellular osmolarity that leads to proximal renal tubular dilatations. Lipoic acid (LA) has antioxidant and anti-inflammatory activities. Bosentan is a competitive endothelin A (ETA) and endothelin B (ETB) receptors antagonist. In this study, the evaluation of effectiveness of lipoic acid and bosentan against diclofenac-induced AKI was done by histopathological examination. The results showed that diclofenac caused histopathological changes include; retracted glomerulus, tubular cast, tubule-interstitial inflammation and tubular necrosis. Lipoic acid or bosentan alone could not reduce the histopathological alterations caused by diclofenac. Meanwhile, the combination therapy was able to reduce the histopathological changes significantly (p>0.05). Therefore, the combination therapy of lipoic acid and bosentan showed promising ameliorative effect against diclofenac-induced AKI